Integrative SER Model: Transformative Optimization of Religious Guidance and Counseling Learning - Sihombing, Elsina; Waruwu, Liyus; Sitepu, Yulia; Gulo, Agustinus; Simamora, Lince R.T. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Learning in religious counseling education is still dominated by conventional approaches that are monological, normative, and lack critical reflection, thus having an impact on the low cognitive and affective involvement of participants. This study aims to explore and analyze the potential of the SER (Spirituality-Education-Reflection) approach as an integrative model in optimizing the learning process in religious counseling education programs. The method used is a literature study with a qualitative descriptive approach, analyzing 60 scientific sources published in the 2015–2025 period and relevant to the themes of religious education, critical pedagogy, reflection, and social transformation. The results of the study show that the SER approach is able to present a participatory, contextual, and transformative learning process. The spirituality component forms the basis of values, education directs an experiential dialogical process, and critical reflection bridges awareness between values and actions. These three elements form praxis as a conscious action that has an impact on personal and social change. In conclusion, the implementation of SER requires curriculum support, extension training, holistic evaluation, and contextual and participatory institutional policies. The implications of this research include strengthening the capacity of religious extension workers, curriculum design reform, and cross-sector collaboration in the sustainable implementation of SER. Further research can be directed to the implementation test of the SER model in various religious education contexts as well as the development of evaluation instruments based on spiritual and social reflection.